Entrepreneurialism and society : consequences and meanings - Eberhart, Robert N.; Lounsbury, Michael; Aldrich, Howard (Bingley, U.K. : Emerald Publishing Limited, 2022)
The second of two volumes bringing together researchers from an array of disciplines including sociology, organization theory, strategy, and organizational behaviour, Entrepreneurialism and Society: Consequences and Meanings addresses the question of how entrepreneurship has transformed from an organizing activity into an ideology that is changing society. The authors investigate how the transformed meanings of entrepreneurship are causal in new social phenomenon such as organizational misconduct and driving inequality, but also how it may offer a promise to resolve those issues. Examining into the role of organizations in society, Entrepreneurialism and Society invigorates academic research by developing new perspectives on how entrepreneurs and their organizations shape our social world.
Introduction - "reversing entrepreneurship's arrow": The metaphor's model and research implications / P. Deveraux Jennings, Timothy R. Hannigan, and Jennifer E. Jennings -- Chapter 1. Towards an untrepreneurial economy? The entrepreneurship industry and the rise of the veblenian entrepreneur / Rasmus Koss Hartmann, Andre Spicer, and Anders Dahl Krabbe -- Chapter 2. Revisiting the relationship between income equality and entrepreneurship: A social trust perspective / Ryan Coles, Shon R. Hiatt, and Wesley D. Sine -- Chapter 3. Rethinking social capital: Entrepreneurial ecosystems as contested communities / Banu Ozkazanc-Pan -- Chapter 4. Social entrepreneurship and the common good / Helen M. Haugh and Bob Doherty -- Chapter 5. How do founding teams form? Towards a behavioral theory of founding team formation / David R. Clough and Balagopal Vissa -- Chapter 6. Enacting (new) possibilities of living: Entrepreneurship and affirmation / Dillon Berjani, Karen Verduijn, and Elco van Burg -- Chapter 7. Entrepreneurship education in post-soviet higher education systems: Moving into or resisting global entrepreneurial culture / Pavel Sorokin, Isak Froumin, and Svetlana Chernenko.
Includes bibliographical references and index.
Print version record.
Keywords: elektronické knihy; electronic books; Entrepreneurship -- Social aspects; Business & Economics -- Entrepreneurship; Entrepreneurship